Plato - Hare, R. M. (Richard Mervyn) (New York : Oxford University Press, 1982)
Relates the problems which led Plato to become a philosopher.
Includes bibliographical references and index.
Booklist.
Wilson's Public Library.
Wilson's Senior High School.
Young Adult
Keywords: Plato; Plato